DOP78 Efficacy of vedolizumab in perianal Crohn's disease: the BioLAP multi-centre observational study. (25th January 2019) - Biron, C; Seksik, P; Nachury, M; Nancey, S; Bouhnik, Y; Serrero, M; Armengol-Debeir, L; Buisson, A; Tran Minh, M-L; Zallot, C; Fumery, M; Bouguen, G; et al.
Abstract: Background: New therapeutic options for Crohn's disease (CD) patients with perianal lesions failing anti-tumour necrosis factor (TNF) therapy are needed. To date, no dedicated study with a large sample has evaluated the efficacy of vedolizumab on perianal CD (pCD). We assessed the efficacy of vedolizumab in pCD in a multi-centre cohort and the predictive factors of success of the biological agent. Methods: We conducted a French multi-centre, and observational study (Bio-LAP) including all patients with either active or inactive pCD (but with history of fistulizing and drained perianal lesion over the past 10 years) who received vedolizumab. In patients with active pCD at treatment initiation, the success of the biological agent was defined by clinical recovery at 6 months of treatment assessed by physician's appreciation without using additional medical or surgical treatment for perianal lesions. In patients with inactive pCD at treatment initiation, clinical recurrence of pCD was defined by the occurrence of perianal lesions and/or need of medical or surgical treatment. Results: In total, 151 patients were screened. There were 49 (32.5%) males, the mean age at inclusion was 39.5 years, the mean BMI was 22.4, the mean duration from CD diagnosis to initiation of treatment was 14.9 years. 149/151 (98.7%) have had at least 1 anti-TNF agent, a total of 143/151 (94.7%) patients had been exposed to thiopurine and/or methotrexate. Ten (6.6%) patients had previous exposure to ustekinumab. The mean number of prior perianal surgery was 2.4. The mean follow-up time was 86 weeks. Ninety-eight patients (64.9%) discontinued therapy after a mean time of 284 days. In patients with active pCD at initiation, 61/102 (59.8%) patients had setons at initiation and vedolizumab success was reached in 23/102 (22.5%) patients. Among patients with setons at initiation, 9/61 (15%) patients had a successful seton ablation during follow-up. In multi-variate analysis, factors associated with success were the number of prior biological agents (3 or more, OR: 0.13; 95% CI: 0.02–1.09; p = 0.018) and antibiotics at initiation (no antibiotics, OR: 4.12; 95% CI: 1.06–15.98; p = 0.024). In patients with inactive pCD at initiation, the mean follow-up time was 131 weeks, perianal disease recurred in 15/49 (30.6%) patients and 11/49 (22.4%) patients needed medical and/or surgical treatment for perianal disease. Mean time to recurrence was 26 weeks. Conclusions: Numerous treatment cessations and perianal disease recurrences under vedolizumab raise the question of the efficacy of anti-integrins at anal canal site. This study warrants further evaluation in dedicated prospective clinical studies to precise the role of vedolizumab in relation to other biological therapies for the management of refractory pCD.